Prospective measurement of outcomes and complications of tibial tuberosity advancement using novel mini plates in small breed dogs - Miller, Leah; Maritato, Karl C.; Kennedy, Shawn C. (Frontiers in Veterinary Science, 2023)
Cranial cruciate ligament (CrCL) disease is a common orthopedic disease in canine patients. Tibial osteotomy procedures for the treatment of cranial cruciate ligament disease in small breed dogs (<15 kg) have previously been limited. A total of 22 client-owned dogs, 26 stifles, with cranial cruciate ligament disease were treated with novel mini-tibial tuberosity advancement plates. The most common intraoperative complications included the need for plate-cage overlap in 7 stifles (26.92%) and screw head fracture in 1 (3.85%). Post-operative complications included tibial tuberosity fracture (3.85%), post-operative medial patella luxation (7.69%), and persistent lameness (7.69%). Of the 26 stifles evaluated in the medium term (>6–12 months) post-operatively, 92.3% had no lameness, with the remaining 7.7% having Grade 1 lameness. A good to excellent clinical outcome was noted in all 26 stifles that underwent TTA with novel mini plates.